THE POSITION OF SPORTS-RECREATIONAL TOURISM IN MONTENEGRO - Ognjen Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
Basic for realization of tourist movements lays in meeting cultural and recreati- onal needs of potential customers. If we know that largest number of tourists represents part of recreational ones, than is not hard to realize how large potential lays in that number of potential guests. On this fact should be built strategy of movement of tourist offer of Montenegro for it extreme potentials on which can be founded concrete project. In this work are given basic assumptions for development of sport recreational shapes of tourism with stress to natural potentials that directly determine shape of sport recreational activities that represent basis of tourist offer. Offer should be created in that way that it is adapted to wide segment of recreational guests and not professional sportsmen, although they also should not be underestimated but one should know that in order to create conditions for arrival of sports professionals offer has to be completely different and more specialized that requires creating of conditions of existence of highly developed sports infrastruc- ture, while for amateurs a lot can be done in "system of improvising", satisfying basic criteria - recreation in conditions of untouched and well preserved nature with securing maximal level of security and protection of guests, in order to prevent possible unwilling consequences that can lead to injury of guests and for development and realization of such project one need a much less funds than is building of facilities that should meet standards of professional sportsmen. The aim is to create good offer at good infrastructure, logistics and with good equipment with securing maximal security, adaptation to various wishes of guests, ta- king in consideration their structure is conditioned by age, health condition, physical fitness as personal wishes toward sports and recreational activities.